Chronic exertional compartment syndrome in athletes: A narrative review - Gaehwiler, R.; Hirschmueller, A.; Grumann, T.; Tiernan, P.; Isaak, A.; Thalhammer, C. (Swiss Sports & Exercise Medicine, 2020)
Abstrac Chronic exertional compartment syndrome of the lower leg accounts for approximately 75% of sports-related chronic leg pain. Nevertheless, the exact and timely recognition in athletes might pose a great challenge to sports physicians. Among a variety of possible differential diagnoses such as tenosynovitis, stress fractures, periostalgia, or popliteal artery entrapment syndrome the physician has to be able to identify the correct entity as promptly as possible. Consequently, profound knowledge about exercise-associated pathologies of the musculoskeletal, nervous and vascular system, as well as the capability of interdisciplinary thinking are critical. Within the course of this narrative review the authors would like to equip the reader with a comprehensive overview about one of the most important entities of non-traumatic lower leg pain in sports medicine. Hence, chronic exertional compartment syndrome of the leg is going to be looked at from different perspectives such as epidemiology, sports at risk, potential explanations of pathophysiology, current and prospective diagnostic procedures, as well as the latest therapeutical options.